Feasibility of returning custody of the mother by separation from the second wife - Seyyed Sajjad mohammadi; Seyyed Abolfazl Mousavian; Ahmad Mortazi (پژوهش‌نامه حقوق اسلامی, 2020)
The jurists agree if the mother who has the custody of her child is married toa person other than her father's father, the custody of the mother will becanceled. If the mother divorces her from her remarriage, there isdisagreement over the return or non-return of the custody of the mother.Many Imams and Sunni jurisprudents believe that the divorce of a motherfrom a barbarian man comes back to her custody. In their view, the mother'sremarriage is a barrier to the exercise of custody, and it is prohibited bydeterioration. In contrast to Maliki's jurisprudents and some of the Imami'sjurists, it is believed that the remarriage of a mother with a felonious manwill be lost to the custody and will not be divorced. It seems that theemergence of narratives, the rule of irreversibility of the right ofimpoverishment, and the fall of the will of the fall, implies that the right ofcustody of the mother does not return to separation from the new wife.